Assessing Clinical Decision-Making Knowledge Among Medical Students Across Academic Levels: A Cross-Sectional Study - Petrovic, Marko; Kovacevic, Ana; Nikolic, Jovana; Jovanovic, Stefan; Marinkovic, Filip (Omni Health Journal, 2026)
Background: Clinical decision-making is a fundamental competency in medical practice that influences diagnostic accuracy, treatment effectiveness, and patient safety. Although clinical reasoning and decision-making have been widely discussed in medical education, evidence regarding the baseline level of clinical decision-making knowledge among medical students remains limited. Understanding students’ knowledge is essential for identifying educational needs and supporting curriculum development. Objective: This study aimed to assess the level of clinical decision-making knowledge among medical students and to examine the association of academic level and gender with knowledge scores. Methods: A quantitative cross-sectional study was conducted among undergraduate medical students at a medical faculty. Stratified random sampling based on academic level was employed to ensure proportional representation of preclinical and clinical students. Of 170 eligible students, 150 completed the questionnaire (response rate: 88.2%). Results: Most respondents demonstrated a moderate level of clinical decision-making knowledge (53.3%), followed by high (26.7%) and low (20.0%) levels. Clinical students achieved significantly higher mean knowledge scores than preclinical students (75.4 ± 8.2 and 70.1 ± 7.5; p = 0.003). Multivariable analysis identified academic level as the strongest factor associated with clinical decision-making knowledge, whereas gender showed no significant association (p = 0.421). These findings suggest that clinical exposure contributes positively to the development of decision-making knowledge among medical students. Conclusion: Medical students generally possess a moderate level of clinical decision-making knowledge. Academic level was significantly associated with knowledge scores, highlighting the importance of clinical exposure and experiential learning in competency development. Strengthening simulation-based learning, case-based discussions, and structured feedback may further enhance clinical decision-making competence among medical students.